Explanation and verification of the rules of attack in table tennis tactics - Xingdong Zhou (BMC, 2022)
Abstract Background The rules of attack in table tennis tactics have been discovered by the coaches and researchers of the Chinese table tennis team (CTTT) through long-term practice. However, they are only empirical judgements and have not been objectively verified. Methods The software "Table Tennis Master" has been used to analyse 200 matches of top players of CTTT against various opponents in recent years to obtain detailed statistics by analysing the effect of attack in the end line (AIEL) and attack out of the end line (AOEL). Results (1) The scoring rate of the players was high after AIEL but very low after AOEL (p < 0.05); (2) the round of service (serve/receive) and level of skills had little influence on the effect of AIEL and AOEL; and (3) the timing of attack had a great influence on the effect of AIEL and AOEL (r > 0.9). Conclusions In the high-level table tennis match, the rules of AIEL and AOEL are scientific. In accordance with the rules, the complex tactics can be simplified to the two concepts, AIEL and AOEL.